2021
DOI: 10.3390/cells10020226
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Chemokines in Atherosclerosis

Abstract: Atherosclerosis is a long-term, chronic inflammatory disease of the vessel wall leading to the formation of occlusive or rupture-prone lesions in large arteries. Complications of atherosclerosis can become severe and lead to cardiovascular diseases (CVD) with lethal consequences. During the last three decades, chemokines and their receptors earned great attention in the research of atherosclerosis as they play a key role in development and progression of atherosclerotic lesions. They orchestrate activation, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 150 publications
(79 reference statements)
2
84
0
Order By: Relevance
“…It is well established that vascular endothelial cell activation with TNFα triggers production of a wide array of leukocyte-recruiting chemokines. Among these, MCP-1/CCL2 and RANTES/CCL5 have been shown to play a critical role in mononuclear leukocyte arrest and participate in the progression of atherosclerotic lesions [29,30]. In the present study, CITCO inhibited TNFα-elicited MCP-1/CCL2 and RANTES/CCL5 release, an effect blunted in cells lacking CAR, suggesting that CAR activation decreases leukocyte arrest by inhibiting chemokine generation and release.…”
Section: Discussionsupporting
confidence: 54%
“…It is well established that vascular endothelial cell activation with TNFα triggers production of a wide array of leukocyte-recruiting chemokines. Among these, MCP-1/CCL2 and RANTES/CCL5 have been shown to play a critical role in mononuclear leukocyte arrest and participate in the progression of atherosclerotic lesions [29,30]. In the present study, CITCO inhibited TNFα-elicited MCP-1/CCL2 and RANTES/CCL5 release, an effect blunted in cells lacking CAR, suggesting that CAR activation decreases leukocyte arrest by inhibiting chemokine generation and release.…”
Section: Discussionsupporting
confidence: 54%
“…In the peripheral blood of patients with cardiovascular diseases a higher share of effector memory T cells (TEM cells or TEM) characterized as CD3 + CD4 + CD45RA − CD45RO + CCR7 − were found, which relate to the degree of atherosclerotic lesions in the coronary and brain carotid regions [39]. In comparison with these results, other studies have demonstrated a CCR7 − T cell elevation in patients with coronary artery disease [40], and T cell memory increase in patients with subclinical carotid atherosclerosis [41].…”
Section: Circulating T Cell Subpopulationsmentioning
confidence: 82%
“…Given that macrophages-related inflammation and lipid accumulation play essential roles in AS ( Poznyak et al, 2020 ; Gencer et al, 2021 ), we further explored whether TDP43 is involved in these biological processes. To verify this hypothesis, TDP43 specific siRNAs were synthesized.…”
Section: Resultsmentioning
confidence: 99%